2022
DOI: 10.1177/03635465211072261
|View full text |Cite
|
Sign up to set email alerts
|

Utility of VOMS, SCAT3, and ImPACT Baseline Evaluations for Acute Concussion Identification in Collegiate Athletes: Findings From the NCAA-DoD Concussion Assessment, Research and Education (CARE) Consortium

Abstract: Background: The Vestibular/Ocular-Motor Screening (VOMS) is a valuable component of acute (<72 hours) sports-related concussion (SRC) assessments and is increasingly used with the Immediate Post-concussion Assessment and Cognitive Testing (ImPACT) instrument and the third edition of the Sport Concussion Assessment Tool (SCAT3). Research has suggested that VOMS acute postinjury scores are useful in identifying acute concussion. However, the utility of preseason baseline measurements to improve diagnostic acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 62 publications
(134 reference statements)
0
38
0
Order By: Relevance
“…Value of baseline testing —Seven papers examined the value of baseline testing using the SCAT. In four studies, neither the SCAT2, SCAT3, nor SCAT5 showed an increased value of baseline testing over standard normative and clinical evaluation 52 56 59 60. One paper did show that for the 5-item word list delayed recall portion of the SCAT2, control athletes improved their performance significantly over baseline (consistent with a practice effect), whereas the concussed group did not show an improvement 20.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Value of baseline testing —Seven papers examined the value of baseline testing using the SCAT. In four studies, neither the SCAT2, SCAT3, nor SCAT5 showed an increased value of baseline testing over standard normative and clinical evaluation 52 56 59 60. One paper did show that for the 5-item word list delayed recall portion of the SCAT2, control athletes improved their performance significantly over baseline (consistent with a practice effect), whereas the concussed group did not show an improvement 20.…”
Section: Resultsmentioning
confidence: 97%
“…The data show that while the overall SMD was lower when collapsed across time points, the greatest differences can be seen within the first 48-hours post-injury. Twenty studies using baseline/post-injury paradigms and including matched controls examined the ability of various iterations of the SAC to assist with the diagnosis of SRC 42–61. Large effects were found when the SAC was administered immediately following concussion 42.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normative data provided herein, with stratifications by gender and preexisting health conditions related to baseline symptom reporting, 9,26 provide a reference point for clinicians to help determine what symptom experience may be typical for a student of the same gender with the same health history. This approach may be more accessible than preseason baseline evaluations to assess symptom change, 3 in that baseline symptom evaluations have poor incremental validity beyond postinjury assessments, 19 symptom scores have poor test-retest reliability, 44 and there is a substantial financial and time burden associated with baseline assessments of many student-athletes who will never experience an injury. Prior researchers have recommended symptom checklists, such as the PCSS, in place of baseline assessments for guiding return to play decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also had no way of blinding participants to their exposure (heading, sham, or control), which could induce alterations to sympathetic and parasympathetic tone, thereby changing absolute heart rate and potentially HRV metrics. The SCAT3 has recently been shown to have only moderate reliability and specificity in diagnosing concussion and post-concussive symptoms (64) and, thus, its utility in the context of this study can be questioned. Moreover, as the SCAT3 relies on subjective self-report, participants may have been more likely to report symptoms knowing they had just been exposed to a controlled bout of repeated head impacts.…”
Section: Limitationsmentioning
confidence: 96%